Factors Associated with the Unplanned Pregnancy at Suhul General Hospital, Northern Ethiopia, 2018 - Yohannes Moges; Solomon Adanew Worku; Abrhaley Niguse; Bayew Kelkay (Journal of Pregnancy)
Background. Unplanned pregnancy is a fundamental concept that is used to recognize the fertility of populations and the unmet need for contraception and family planning. Unplanned pregnancy happened mainly due to the results of not using contraception or inconsistent or incorrect use of effective methods. Reducing the number of unplanned pregnancy endorses reproductive health mainly by reducing the number of times a woman is exposed to the risk of pregnancy and childbearing. Objective. This study is aimed at assessing the magnitude of unplanned pregnancy and associated factors among pregnant mothers attending antenatal care at Suhul General Hospital, Northern Ethiopia. Methods. A facility-based cross-sectional study design was conducted among pregnant mothers visiting antenatal care follow-up from February to April 2018 at Suhul General Hospital, Shire, and Northern Ethiopia. The study participants were selected using a systematic sampling method, and the data was collected using a pretested structured questionnaire through face-to-face interviews. Bivariate and multivariate logistic regression analyses were done to determine the association of each independent variable with the dependent variable. Result. The magnitude of unplanned pregnancy among 379 pregnant mothers was 20.6%. Unmarried women [AOR: 4.73, 95% CI: (1.56, 14.33)], age above forty [AOR: 4.17, 95% CI: (1.18, 14.6)], had no history of unplanned pregnancy [AOR: 3.26 95% CI: (1.65, 6.44)], and unemployed [AOR: 6.79; 95% CI: (2.05, 22.46)] were the variables significantly associated with the magnitude of unplanned pregnancy. Conclusion and Recommendation. The findings of this study showed that the magnitude of unplanned pregnancy was high and age, marital status, occupation, and history of unplanned pregnancy were statistically associated with an unplanned pregnancy. There is seeming necessity to plan strategies of communication within couples or individuals on reproductive especially on fertility and promote family planning methods.